Relationship of Abnormal Heart Rate Turbulence and Elevated CRP to Cardiac Mortality in Low, Intermediate, and High-Risk Older Adults. - STEIN, PHYLLIS K.; BARZILAY, JOSHUA I. (Journal of Cardiovascular Electrophysiology, 2011)
. (J Cardiovasc Electrophysiol, Vol. 22, pp. 122-127, February 2011)